Analisis Deskriptif Gaya Manajemen Konflik dan Profil Kesejahteraan Psikologis Peserta didik kelas 9 MTs An-Nuriyah - Nur Amanah Billa; Devi Ratnasari; Budi Purwoko; Evi Winingsih (LPPM Institut Pendidikan Nusantara Global, 2026)
Adolescence is a critical developmental period characterized by emotional instability, identity exploration, and increased vulnerability to interpersonal conflict, particularly within school environments where peer interactions are intensive. In Madrasah Tsanawiyah (MTs), which integrate academic and religious education, empirical studies examining students’ conflict management styles and psychological well-being remain limited, underscoring the urgency of context-specific research. This study aimed to identify the dominant conflict management styles and to map the strengths and weaknesses of psychological well-being dimensions among ninth-grade students at MTs An-Nuriyah, as a basis for educational and psychosocial intervention planning. A quantitative descriptive design was employed, involving 60 ninth-grade students selected through simple random sampling. Data were collected using a conflict management style questionnaire based on the Thomas–Kilmann model and a psychological well-being scale adapted from Ryff’s (1989) six-dimensional framework. The results indicated that avoiding (M = 3.85) and collaborating (M = 3.84) were the most dominant conflict management styles, followed by compromising and accommodating, while the competing style demonstrated the lowest mean score. The psychological well-being profile revealed strong dimensions in positive relations with others, personal growth, and environmental mastery, with relatively lower levels of autonomy and self-acceptance. These findings suggest that although students tend to adopt harmonious and cooperative approaches to conflict, they may experience limitations in independent decision-making and self-evaluation. Practically, the results highlight the need for school-based guidance and counseling programs that strengthen autonomy and self-acceptance while fostering assertive and constructive conflict management skills to support optimal psychological development during adolescence.